(untitled) (International journal of medical sciences, 2026)
Disease prevention is a fundamental objective of modern healthcare systems. While prevention is often associated with vaccination, sanitation, and health promotion, treatment work also plays a decisive role in preventing disease progression, recurrence, complications, and transmission. This article examines the theoretical foundations and practical mechanisms through which treatment interventions contribute to primary, secondary, and tertiary prevention. Drawing upon conceptual frameworks developed by the World Health Organization and the Centers for Disease Control and Prevention, the study analyzes the integration of therapeutic services into preventive strategies. The paper highlights clinical management, early diagnosis, rehabilitation, and patient education as key components of treatment work that strengthen public health outcomes. The findings demonstrate that effective treatment not only cures illness but also significantly reduces morbidity, mortality, economic burden, and health inequalities.